Síndrome de Gorlin-Goltz: características sistêmicas e maxilofaciais - Matos, Jefferson David Melo de; Nakano, Leonardo Jiro Nomura; Diamantino, Pedro Jacy Santos; Lopes, Guilherme da Rocha Scalzer; Bottino, Marco Antonio; Vasconcelos, John Eversong Lucena de; Ramos, Nathália de Carvalho; Andrade, Valdir Cabral (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Gorlin-Goltz Syndrome, also known as Nevoid Basal Cell Carcinoma Syndrome, is a rare genetic disorder characterized by the presence of multiple keratocysts in the jaw and basal cell carcinomas, at young age, of palmar and/or plantar depressions, of calcification of the sickle cerebral and skeletal malformations. This syndrome is caused by a mutation of the PTCH1 (patched homolog 1 from Drosophila) gene, a tumor suppressor gene. In this work, the systemic and maxillofacial characteristics of the Gorlin-Goltz syndrome, as well as some neurological, dermatological, musculoskeletal and endocrine alterations, are reviewed. In addition, a case report was added for the purpose of support this study.